Evaluation by electron microscopy and anaerobic culture of types of rumen bacteria associated with digestion of forage cell walls. - Akin, D E (1980)
Different morphological types of rumen bacteria which degraded cell walls of forage grasses with various in vitro digestibilities were evaluated with electron microscopy. The majority of these bacteria (i.e., about 70% or more) consisted of two distinct types: (i) encapsulated cocci and (ii) irregularly shaped bacteria, resembling major fiber digesters found in the rumen. Each type was capable of degrading structurally intact cell walls. Differences (P less than or equal to 0.02) in the percent ratio of encapsulated cocci to irregularly shaped bacteria were observed between Bermuda grass and fescue; the ratio of encapsulated cocci to irregularly shaped bacteria between Bermuda grass and orchard grass was similar and variations were high. The proportion of irregularly shaped bacteria usually increased with increased time of digestion. Differences (P greater than 0.1) were not found in the percentage ratio of encapsulated cocci to irregularly shaped bacteria attached to specific tissue types in either Bermuda grass or fescue. However, encapsulated cocci tended to be more prevalent on sclerenchyma than other tissues in Bermuda grass, but less prevalent on sclerenchyma than other tissues in fescue. Transmission electron microscopy of tissue digestion of rapidly degraded orchard grass blades revealed that mesophyll, parenchyma bundle sheath, and parts of the epidermal cell wall apparently were degraded without direct attachment of bacteria although bacteria were near the cell walls undergoing digestion. Anaerobic growth studies showed that the total culturable bacteria developing on medium 10 and media containing carbohydrates similar to those in forage cell walls (i.e., pectin, xylan, and cellobiose) were 80% higher from rumen bacterial populations adapted in vitro to cell walls of orchard grass compared to those from Bermuda grass; the number of colonies from the orchard grass-adapted population was significantly (P less than or equal to 0.05) greater on the medium containing xylan. Filter paper tests showed that the cellulolytic activity of populations adapted to fescue was greater than that of orchard grass or Bermuda grass.